PIV measurement of flow field generated during noisy film boiling in saturated He II. (June 2020) - Murakami, M.; Takada, S.
Highlights: PIV technique successfully applied to He II noisy film boiling. Large-scale boiling bubble is not a single bubble, but is composed of an infinite number of micro-bubbles. In response to growth and collapse of bubble mass, a standing alternating flow is induced. Three kinds of steady underlying flow components, thermal counter flow, plume and entrainment. Abstract: Noisy film boiling in nearly saturated He II caused by heating from a flat plate heater placed horizontally was investigated by applying visualization method and PIV (Particle Image Velocimetry) using hydrogen-deuterium solid particles as tracer particles. The images taken by a high-speed video to be used for the PIV were also used for visualization study, and the appearance of generation, growth and collapse processes of mass of tiny bubbles caused due to boiling and the qualitative aspect of the flow field could be understood. By the application of the PIV technique, the frequency of growth and collapse of bubble mass and the flow velocity field formed in the surrounding He II were measured. The output from the PIV was further examined separately for the time average and the time fluctuating components, and in each, independent flow components were identified. It was shown that the steady flow components include the plume above the heater and the entrainment towards the plume as well as the thermal counterflow. And the standing radially alternating flow is induced by repeatedly growing and collapsing bubble mass as a fluctuating flow. Their superposition forms the surrounding flow field.